Determination of HMGB1 in hepatitis B virus-related acute-on-chronic liver failure patients with acute kidney injury: Early prediction and prognostic implications - Liu, Yu; Yuan, Wei; Fang, Miao; Guo, Hongying; Zhang, Xin; Mei, Xue; Zhang, Yuyi; Ji, Longshan; Gao, Yating; Wang, Jiefei; Qian, Zhiping; Li, Man; et al. (Frontiers in Pharmacology, 2023)
Background: Acute kidney injury (AKI) is a frequent complication in patients with hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) and is associated with high rates of mortality. We aimed to estimate serum high mobility group protein 1 (HMGB1) levels in HBV-ACLF patients and analyze their clinical value in the development and outcomes of AKI. Methods: A total of 251 consecutive patients with HBV-ACLF were enrolled in this retrospective study. Using the International Club of Ascites staging criteria of AKI, 153 patients developed AKI. The clinical data of patients were collected and serum levels of HMGB1 were measured by ELISA. All patients were followed up until death or for a minimum of 3 months. Early prediction and prognostic implications of HMGB1 in Hepatitis B Virus-Related Acute-on-Chronic Liver Failure Patients with Acute Kidney Injury were investigated in different cohorts, including a propensity score-matched ACLF cohort. Results: Among all individuals with HBV-ACLF, the incidence of AKI was 61.0% (153/251). The patients who developed stage 2/3 AKI showed the highest HMGB1 levels, followed by those who developed stage 1 AKI, and those without AKI showed the lowest HMGB1 levels. Moreover, HMGB1 levels were significantly higher in non-survivors than in survivors among HBV-ACLF patients with AKI. Furthermore, analysis of the area under the receiver operating characteristic curve (AUROC) indicated that serum HMGB1 levels (pre-matching: AUC = 0.740; post-matching: AUC =0.661) may be a potential predictive factor for AKI development and that HMGB1 (AUC=0.727) might be a reliable biomarker for prognosis in patients with AKI. Conclusions: In patients with HBV-ACLF, AKI is universal. AKI and its stages negatively influence the 90-day transplant-free mortality rate. Serum HMGB1 levels can serve as a positive predictor of AKI development, and HMGB1 might also be a prognostic biomarker for AKI among HBV-ACLF patients.